Weight/carapace length relationship and condition factor of the roughneck shrimp, Rimapenaeus constrictus (Stimpson, 1874), on the southeastern Brazilian coast - Da Silva, Alexandre R.; Lopes, Ana Elisa B. [UNESP]; Grabowski, Raphael C. [UNESP]; Castilho, Antonio L. [UNESP] (Acad Brasileira De Ciencias, 2021)
Rimapenaeus constrictus is a penaeid shrimp widely distributed in the Western Atlantic, frequently captured as bycatch in trawling activities. Here we describe the weight vs. carapace length relationship and the condition factor of the species. Shrimps were sampled in the Ubatuba region, northern littoral of Sao Paulo State, monthly. We analyzed 4,952 individuals (1,371 males and 3,581 females). We measured the individuals' weight and carapace length, and the condition factor (CF) was calculated for both sexes. Females had a heavier body when compared to males, probably due to their greater maximum body size achieved. Both sexes presented a negative allometric growth in weight, probably due to their reproductive pattern and activities. We found similar mean CF values for males and females. From temporal analysis, the highest CF values for females were observed during the seasons with lower water temperatures. Such a situation may happen because females' CF tend to be influenced by a greater food availability in the environment, induced by the intrusion of the South Atlantic Central Water during the spring and early summer in the Ubatuba. The information presented here could be used as subside in protection actions and management of bycatch species.
Keywords: Allometry; degree of fattening; Penaeidae; wellness